2021
DOI: 10.29259/jep.v19i1.13826
|View full text |Cite
|
Sign up to set email alerts
|

Public Infrastructure and Economic Growth in the Local Region

Abstract: This study aims to analyze the effect of public infrastructure on economic growth in Lampung Province. The data used are time series and cross sections for the period 2012-2018 and 14 districts/cities. The method applied is the panel data model with the random effect model method. The results showed that Infrastructure, Irrigation Infrastructure, Health Infrastructure, Investment, Labor, and Gini Growth had a significant and positive effect on economic growth, while capital expenditures insignificant effect on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
(11 reference statements)
0
0
0
Order By: Relevance
“…Seprillina, Yusida, Narmaditya, and Chung (2021), who researched the effects of the construction of toll road gates in Malang, showed that the existence of toll road gates has yet to be able to increase people's income and expenses. Different from the results of research by Respitasari (2021), which explains that road, irrigation, and health infrastructure are essential to encourage economic growth.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Seprillina, Yusida, Narmaditya, and Chung (2021), who researched the effects of the construction of toll road gates in Malang, showed that the existence of toll road gates has yet to be able to increase people's income and expenses. Different from the results of research by Respitasari (2021), which explains that road, irrigation, and health infrastructure are essential to encourage economic growth.…”
Section: Introductionmentioning
confidence: 68%
“…However, those resources have not been supported by adequate infrastructure (Weya, Nopeline, & Damanik, 2021). Therefore, enhancing Indonesia's infrastructure development remains to be a challenge, especially the development of regional potential (Respitasari, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, establish a technology network to accelerate the process of reporting, communication and execution of infrastructure improvements. However, in social reality there is still a tendency towards difficulties in reaching transportation access to support mobility [39]. Source: [40] The data presents the condition of digitizing infrastructure in each Indonesian province, and Lampung itself occupies the 33.19th position or the 30th position of all provinces.…”
Section: %mentioning
confidence: 99%